Animating the Language Machine: Computers and Performance. - Soules, Marshall (Computers & the Humanities, 2002)
A range of inter-disciplinary discourses consider the computer-mediated writing space as a unique performance medium with characteristic protocols. Drawing on contemporary performance theory, literary criticism, and communication theory, the author proposes that technologists, academics, and artists are developing idiomatic rhetorics – a lingua franca – to explore the technical and expressive properties of the new ``language machines'' and their hypertextual environments. The role of improvisation – and its cross-disciplinary protocols – provides a further focus in the discussion of computing practice and performance.